2020
DOI: 10.3389/fpsyg.2019.02992
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and Experiences of Couples Receiving Therapy Through Videoconferencing: A Qualitative Study

Abstract: Videoconferencing is an emerging medium through which psychological therapy, including relationship interventions for couples, can be delivered. Understanding clients' expectations and experiences of receiving therapy through this medium is important for optimizing future delivery. This study used a qualitative methodology to explore the expectations and experiences of couples throughout the process of the Couple CARE program, which was delivered through videoconferencing. Fifteen couples participated in semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…Indeed, these benefits parallel many of the experiences shared by our participants in the themes of safe therapeutic space and convenience . Specifically, convenience and comfort of engaging in relational teletherapy from one's home environment or “safety zone” (Kysely et al, 2020), reduced waiting room anxiety, and time‐saving benefits were expressed throughout both themes for the current study. Although one of the main teletherapy training barriers discussed in the MFT literature involves time consumption and financial cost for graduate programs (Cravens Pickens et al, 2019), the juxtaposition is that these economic and time‐saving benefits are what clients often cited as advantageous to their participation in relational teletherapy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, these benefits parallel many of the experiences shared by our participants in the themes of safe therapeutic space and convenience . Specifically, convenience and comfort of engaging in relational teletherapy from one's home environment or “safety zone” (Kysely et al, 2020), reduced waiting room anxiety, and time‐saving benefits were expressed throughout both themes for the current study. Although one of the main teletherapy training barriers discussed in the MFT literature involves time consumption and financial cost for graduate programs (Cravens Pickens et al, 2019), the juxtaposition is that these economic and time‐saving benefits are what clients often cited as advantageous to their participation in relational teletherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Findings from this study also suggest that family‐based telehealth interventions are uniquely suited to meet the treatment demands of adolescents without adequate treatment options (Anderson et al, 2017). Furthermore, the experiences of couples receiving teletherapy were explored and reported that couples experienced a positive shift in expectations and specifically noted that teletherapy allowed them to become fully immersed in the therapeutic process (Kysely et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Uniquely, our qualitative results suggest some advantage of TH delivery in family therapy over face-to-face, as reported in previous research with individual or couples therapy (Richardson et al 2015 ). Key factors for perceived efficacy from the client and therapist perspectives include ease of talking in telehealth, where turn taking is clearer, and ease of revealing vulnerability for some clients, invoked by a sense of distance in TH that may be conducive to disclosure (Kysely et al 2020 ). Accessibility is also key.…”
Section: Discussionmentioning
confidence: 99%
“…Kysely et al . (2020) reported findings from 15 couples who had completed a six‐week structured synchronous videoconference‐delivered intervention. Using a version of thematic analysis, they reported that couples had experienced a positive shift in expectations, with many couples’ initial reservations overtaken by their ability to become fully immersed in the therapeutic process.…”
Section: Participants’ Experiences Of Digital Interventionsmentioning
confidence: 99%